(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The research aims at introducing international standards of internal auditing standards, including properties, performance, and special focus on the role of internal auditors abide by the standards of properties in achieving better accountability of the various actors in the Arab Bank and its branches in Jordan. The researcher to gather information on the questionnaire that was designed in accordance with the pivotal first measure the degree of compliance with the standards of properties and the second measures the following criteria for properties to achieve accountability is through the use of statistical methods to researcher concluded that 42.5% of the changes to achieve accountability back to the standard features and more standards influential is the standard independence and objectivity. The researcher recommended the need to increase awareness of the bank’s employees the concept of accountability and its importance in strengthening corporate governance and to determine where the accountability lies and areas, and those which are handled by the methods, within the evidence and issued by the Bank.